A review of deep eutectic solvents (DESs), Preparation, Classification, Physicochemical properties, Advantages and disadvantages - Affat, Sajda (University of Thi-Qar Journal of Science, 2024)
Since deep eutectic solvents (DESs) are readily available, inexpensive, highly biodegradable, and easy to synthesize, they are gaining popularity as a green alternative to hazardous organic solvents and traditional ionic liquids (ILs). DES is a mixture of hydrogen bond donor (HBD) and acceptor (HBA) that is viscous and non-water soluble. There are two main penalty areas of DES fabrication. The first is to reduce its operation temperature to lower that of  these components. The second is to produce a molten salt with a melting point lower than its components. Therefore, DESs are being utilized more and more in a range of analytical chemical applications. Different extraction techniques have been used for this kind of salt. In this review, production methods, and classification of DESs were discussed. The most physical properties of DESs were demonstrated, including melting point, viscosity, density, surface tension, phase changes in behavior, analyte solubility, instrumental compatibility, and toxicity. It also included the main advantages and disadvantages of DES production.